Forum promyshlennikov i predprinimatelei . Forum promyshlennikov i predprinimatelei . Forum of Industrialists and Entrepreneurs . Форум промышленников и предпринимателей - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Boris Yeltsin's speech on the economic situation and reforms in the Russian Federation. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation) Речь Бориса Ельцина об экономической ситуации и реформах в Российской Федерации. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации)